Incorporation of L Cell Sterols into Vesicular Stomatitis Virus - Bates, Sandra R. (1972)
The incorporation of host cell sterol into vesicular stomatitis virus can be effectively studied in an L cell system. The end product of de novo sterol synthesis in the L cell is desmosterol, and as the concentration of cholesterol in the medium is increased the cells incorporate the exogenous cholesterol and the synthesis of desmosterol decreases. L cells which contained desmosterol as their sole sterol produced virus whose sterol content was similarly composed of only desmosterol. Virus grown in L cells which had a constantly changing sterol ratio also contained a mixture of cholesterol and desmosterol, but the virus was found to be more enriched in cholesterol than in the L cells in which it was grown. Viral stability, growth, and plaquing efficiency were tested and found not to be affected by the alteration of its sterol composition, i.e., by partially or completely replacing cholesterol with desmosterol.